Limitations of Explainability for Established Prognostic Biomarkers of Prostate Cancer - Manjang, Kalifa; Yli-Harja, Olli; Dehmer, Matthias; Emmert-Streib, Frank (Frontiers in Genetics, 2021)
High-throughput technologies do not only provide novel means for basic biological research but also for clinical applications in hospitals. For instance, the usage of gene expression profiles as prognostic biomarkers for predicting, e.g., cancer progression, has found widespread interest. Aside from predicting the progression of patients it is generally believed that such prognostic biomarkers provide also valuable information about disease mechanisms and the underlying molecular processes that are causal for a disorder. However, the latter assumption has been challenged. In this paper, we study this problem for prostate cancer. Specifically, we investigate a large number of previously published prognostic signatures of prostate cancer based on gene expression profiles and show that none of these can provide unique information about the underlying disease etiology of prostate cancer. Hence, our analysis reveals that none of the studied signatures has a sensible biological meaning. Overall, this shows that all studied prognostic signatures are merely black-box models allowing sensible predictions of prostate cancer outcome but are not capable of providing causal explanations to enhance the understanding of prostate cancer.